Teachers as transformative agents: an interview of retired teacher mwalimu gatheca from njumbi village, murang’a county. Kenya - Nyambura, Salome (NJINGA e SEPÉ: Revista Internacional de Culturas, Línguas Africanas e Brasileiras (ISSN: 2764-1244), 2023)
The World Teachers day is celebrated globally on 5th October to highlight the rights, responsibilities and standards of teachers in their quest to impact the communities they live in. The first celebration of the World Teachers day was in 1994 to commemorate the anniversary of the adoption of the 1966 ILO/UNESCO Recommendation concerning the status of teachers around the globe (UNESCO[i]). According to UNESCO[ii] the theme for this year was, “The transformation of education begins with the teachers”. In Kenya celebrations were held in various education institutions right from basic to tertiary education. This is the one day, that a teacher is trending and several congratulatory messages are given to teachers by their learners. In this article, we celebrate a retired teacher Mwalimu Gatheca, who hails from a small rural community in Njumbi, which is located in the central part of Kenya. He is a respected elder in his community and though retired, he is not expired. He is still actively engaged in a transformative agenda in his community which has entailed harnessing energies of his community members who cut across gender, age and geographical divide.